Preparation, Physicochemical Evaluation and Antimicrobial Potential of Topical Dosage Forms Containing Natural Anti-inflammatory Agent, Curcuma longa - Dua, Kamal; Kok Leong, Ngai; Kaur, Manprit; Wen Bin, Lim; Azman, Katrina; Gorajana, Adinarayana (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2011)
In an attempt for better treatment of bacterial infections and burn wounds various topical formulations containing 1%w/w of Curcuma longa were prepared and evaluated for physical appearance, pH, rheological properties and stability studies. Antimicrobial activity of prepared formulations was found to be more effective against various strains of bacteria. Carbopol gel base is the most suitable dermatological base for Curcuma longa in comparison to various other dermatological bases. It also has aesthetic appeal, which other bases lack, an important aspect from patient compliance and consumer point of view. The therapeutic potential of such topical formulations may motivate researchers for its further exploitation so that it may be commercially viable. This innovative mode of formulation of Curcuma longa can be employed for enhancing the anti-microbial effect.
Keywords: Topical route